MODEL GERAKAN REKLAIMING TANAH DALAM PERSPEKTIF MASYARAKAT ADAT KASUS DI WILAYAH KABUPATEN KOTAWARINGIN TIMUR - Rusmanto, Joni; Sonia Ulfaritha, Ester (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2021)
Tenure conflicts between indigenous communities and plantation companies are based on differences in the legality of claims. The community as a subsystem of traditional farmers underlies the claim of management rights based on traditional knowledge. On the other hand, plantation companies based the legality of claims based on agrarian law that is normative positivistic with a capitalistic economic orientation. In Henri Lefebvre's perspective, in fact there is no completely